Контури лексико-топонімічної стратиграфії України і етногенез українців - Тищенко, К. (Народна творчість та етнографія, 2005)
The article under consideration states the total combination of linguistic facts which is a generalization of 350 publications on the research of ancient ethnolinguistic contacts of Ukrainian vocabulary and toponymy. The author discusses toponymic facts and lexical borrowings, explains their presence in the Ukrainian language, and in the conclusion gives his view on the succession of the Ukrainian folk through the contacts with its neighbours.